A Syntactic-Semantic Study of English Phrasal Verbs - Mansurova Surayyo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
A verb is a word used primarily to indicate a type of action, such as to fly or to wish, though it may also be used to indicate a general state of existence, such as to live. There is also a special type of verb, known as a copula or linking verb, which helps to describe the subject of the sentence, rather than describing an action. The primary example of this in English is the verb to be which is usually used in the role of linking verb. A verb is one of the basic building blocks of a sentence in most languages, with most grammatical sentences requiring at least one noun acting as a subject, and one verb to indicate an action.